Սուրբ Ներսէս Շնորհալու «Հաւատով խոստովանիմ» աղօթքը. թարգմանութիւն եւ մշակութային փոխանցում - Գասպարեան, Լուիզա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Религиозно-философские труды Св. Нерсеса Шнорали (Нерсес Благодатный) всесторонне изучены десятками ученых и переведены на разные языки мира (более 36), занимая достойное место в мировой литературной и культурной сокровищнице. Целью исследования выступает выявление культурного трансфера в сравнительном ключе на материале переводов (русский, английский, итальянский) молитвы «С Верою Исповедую» Св. Нерсеса Шнорали. Очевидно, что молитва имеет уникальную текстовую структуру, в которой Св. Нерсеса Шнорали представляет двадцать четыре молитвы на каждый час дня. В статье всесторонне освещены структурные и стилистические особенности молитвы, языковые и вне-языковые факторы переводческой деятельности, а также некоторые стратегические принципы трансфера. Обозначается спектр вопросов, связанных с изучением специфики перевода религиозно маркированных единиц в свете парадигмы культурного трансфера. Методологическая основа статьи является концепция культурного трансфера, метод обратного перевода и традиционные для сравнительного литературоведения методики сопоставительного, текстологического и контекстуального анализа. The religious and philosophical works of St. Nerses Shnorali (Nerses the Gracious) were on the agenda of many scientists research works. His spiritual creativity was translated into many languages (more than 36), occupying its honorable place in the world literary and cultural heritage.The purpose of the study is to carry out a research within the framework of St. Nerses Shnorali’s prayer “I Confess with Faith” and to reveal the principles of cultural transfer through the prism of comparison between the original and the translations (Russian, English, Italian). One cannot fail to observe that the prayer has a unique textual structure in which St. Nerses Shnorali illustrates twenty-four prayers for each hour of the day. The research comprehensively focuses on the structural and stylistic features of the prayer, the linguistic and extra-linguistic factors that influenced on the process of translation, as well as some strategic principles of transfer. A range of issues is outlined related to the translation peculiarities of the religiously marked units through the paradigm of the cultural transfer. The methodological basis of the article covers - the concept of cultural transfer, the method of reverse translation, comparative literature, textual and contextual analysis.
Keywords: Ներսես Շնորհալի; Թարգմանություն